Quickest detection of a state-dependent change-point in discrete time. Issue 4 (2nd October 2017) - Cai, Liang; Pan, Li-Yun; Zhang, Huan-Huan; Gao, Ming-Zhong; Wang, Zhi-Nan
ABSTRACT: We study the quickest detection of a change point in a sequence of observations whose prior probability depends on the observed states. By the Bayesian scheme we get the optimal stopping rules under the hybrid probability space.